Respuesta :
Answer:
[tex]\large\boxed{A.\ x=-\dfrac{2}{5}}[/tex]
Step-by-step explanation:
[tex]\dfrac{2}{3}(x-2)=4x\qquad\text{multiply both sides by 3}\\\\3\!\!\!\!\diagup^1\cdot\dfrac{2}{3\!\!\!\!\diagup_1}(x-2)=(3)(4x)\\\\2(x-2)=12x\qquad\text{divide both sides by 2}\\\\\dfrac{2\!\!\!\!\diagup^1(x-2)}{2\!\!\!\!\diagup_1}=\dfrac{12\!\!\!\!\!\diagup^6x}{2\!\!\!\!\diagup_1}\\\\x-2=6x\qquad\text{subtract}\ x\ \text{from both sides}\\\\x-x-2=6x-x\\\\-2=5x\qquad\text{divide both sides by 5}\\\\\dfrac{-2}{5}=\dfrac{5\!\!\!\!\diagup^1x}{5\!\!\!\!\diagup_1}\\\\-\dfrac{2}{5}=x\to x=-\dfrac{2}{5}[/tex]